2006
DOI: 10.1016/j.neuroscience.2006.02.018
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for cyclic guanosine 3′,5′monophosphate signaling in synaptic plasticity: A selective suppressor of protein kinase A-dependent forms of long-term potentiation

Abstract: At excitatory synapses onto hippocampal CA1 pyramidal cells, activation of cyclic AMP-dependent protein kinase and subsequent down-regulation of protein phosphatases has a crucial role in the induction of long-term potentiation by low-frequency patterns of synaptic stimulation. Because the second messenger cyclic guanosine 3′,5′monophosphate can regulate the activity of different forms of the cyclic AMP degrading enzyme phosphodiesterase, we examined whether increases in cyclic guanosine 3′,5′monophosphate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…In addition, baseline synaptic responses were also not altered in cells infused with 8-Br-cAMP (Fig. 5C) (N ϭ 7), consistent with previous studies (Blitzer et al, 1995;Makhinson et al, 2006). To test whether TBP-induced LTP or the associated spine expansion are affected by previous activation of postsynaptic PKA, we loaded pyramidal cells with 8-Br-cAMP for 15-20 min, and then applied TBP.…”
Section: Spine Expansion Occurs But Does Not Persist Under Conditionssupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, baseline synaptic responses were also not altered in cells infused with 8-Br-cAMP (Fig. 5C) (N ϭ 7), consistent with previous studies (Blitzer et al, 1995;Makhinson et al, 2006). To test whether TBP-induced LTP or the associated spine expansion are affected by previous activation of postsynaptic PKA, we loaded pyramidal cells with 8-Br-cAMP for 15-20 min, and then applied TBP.…”
Section: Spine Expansion Occurs But Does Not Persist Under Conditionssupporting
confidence: 87%
“…7D) (140 Ϯ 15%; N ϭ 54 spines/6 cells; p ϭ 0.95 compared with control spine expansion). It has been suggested that PP1 can be endogenously inactivated by PKA (Kang-Park et al, 2003;Makhinson et al, 2006), and so we would anticipate that persistently elevated PKA activity in the postsynaptic cell would have an effect similar to that of okadaic acid. We tested this possibility by including 8-Br-cAMP in the recording pipette solution, and we repeated the above experiments using LFS.…”
Section: Spine Stabilization and Ltp Consolidation Are Both Disruptedmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the discovery that zaprinast serves as a relatively potent GPR35 agonist (Taniguchi et al, 2006) affects the interpretation of data in which zaprinast was assumed to solely affect cGMP degradation. For example, zaprinast induced a significant depression of basal synaptic transmission in rat hippocampus attributed to elevation of the intracellular cGMP level (Monfort et al, 2002;Makhinson et al, 2006). However, our data provide evidence for the potential modulation of presynaptic Ca 2ϩ channels by zaprinast acting as a GPR35 agonist.…”
Section: Discussionmentioning
confidence: 55%
“…Generation of cGMP by NOsGC appears to be a crucial step in NO signaling in the brain (Boulton et al, 1994;Ahern et al, 2002;Monfort et al, 2004;Makhinson et al, 2006). In subcortical areas, several studies demonstrated that the NO-NOsGC-cGMP pathway can either facilitate (Klyachko et al, 2001;Kraus and Prast, 2002;Li et al, 2004) or inhibit (Ozaki et al, 2000) GABAergic neurotransmission.…”
Section: Both Perisomatic and Dendrite Targeting Gabaergic Neurons Comentioning
confidence: 99%